Biotecnologia associada ao óleo essencial de alecrim pimenta na silagem de girassol consorciado com o capim paiaguás - Ferreira, Rafaela Santos (2021)
The objective of this work was to evaluate the effect of nanoformulated Rosemary peppere essential oil of thymol on the silage of sunflower biomass intercropped with Paiaguás grass. The work was conducted at the Federal University of Sergipe (UFS), municipality of São Cristóvão/SE, Brazil. Four additives (control, oil, essential nanoformulated Rosemary pepper, nanoformulated thymol with 62 and 100% purity) were evaluated in the silage of sunflower biomass intercropped with Piaiaguás grass, associated with two silo opening times (15 and 30 days ). The experimental design used was completely randomized, in a 4 x 2 factorial scheme, with five replications. Ethereal extract, neutral detergent fiber and lignin contents were affected (P<0.05) by the additive used. Higher levels of ether extract were recorded in the control silage, followed by 62% and 100% thymol. The mineral matter, crude protein and pH contents were influenced by the interaction between the additive used and the silo opening time. Lower pH values were found in the nanoformulated essential oil, in the opening times of fifteen and thirty days. Lower maximum temperatures were found in 100% thymol, followed by essential oil. The loss of dry matter had the highest content at the opening time of 30 days, while for the dry matter recovery the highest content was at the opening time of 15 days. Higher levels of gas losses were recorded in the control followed by 62% thymol (opening time of 15 days), in the control followed by 100% thymol (opening time of 30 days). Greater effluent losses were recorded in the silage with 62% thymol (15 days silo opening time), in control and 62% thymol (62% silo opening time). The use of essential oil and 100% thymol is shown to be better in reducing fermentation loss and aerobic stability of sunflower silage intercropped with paiaguá grass.